Eurasian Economic Union’s Globalization as a Condition for International Industrial Cooperation Forming - BELYAKOVA, Galina Ya.; BELYAKOV, Sergey A.; POLEJAEVA, Natalya V.; FOKINA, Darya A.; ERIGINA, Liliya V. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).04, 2019)
The international globalization process and development of industrial cooperation are concepts reviewed in this article to describe the most important feature of the modern world economy. In the non-favorable economic environment and increasing competition there are multiple examples creation of Economic Unions, practically everywhere in the world, which demonstrate that it is not an isolated event, but an actual global phenomenon. The domestic enterprises opportunities given by economic integration are growing, so it is require studying the means and ways for their utilization. The main goal in creating an Economic Union is the evolution of regional integration processes. The significance of the fourth stage in economic integration comprises Economic Unions on the modern world can hardly be overestimated. XXI century gave such a high incentive to the development of international integration – Economic unions have become the major players on the world economic scene. The research focused on processes of regional integration and its particular features in the frame of the Eurasian Economic Union formation and their impact on the development of international industrial cooperation in the Union.